(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
The Cerrado biome contains a flora estimated at seven thousand species, which have been under strong anthropogenic action in recent decades. The objective of this paper is to estimate the genetic resources from the Cerrado biome, based on literature review. A total of 270 species from 82 botanical families are reported. The outstanding families were Leguminosae, Asteraceae, Rubiaceae, Bignoniaceae and Euphorbiaceae. The number of species listed represent less than 5% of Cerrado flora, and this is even lower when we only consider species reported in chemical and pharmacologically studies.